WILL SYSTEMS‐OF‐SYSTEMS MODELS SUPPORT COST RECOVERY FOR CRITICAL INFRASTRUCTURE RESILIENCY?. Issue 4 (December 2016) - Harris, William R.
ABSTRACT: The fragility of critical infrastructures and the interdependency of infrastructures such as electric grids, water, wastewater, agriculture and manufacturing supply chains should encourage cost recovery for investments in resilience, not merely system reliability . Most cost recovery standards support investments for safety and reliability, but not resilience. If model‐based systems engineering (MBSE) and virtually all other engineering domains can demonstrate greater system protection, adaptability, and recovery (minimizing cascading harms to connected critical infrastructures), regulatory standards should provide cost recovery for investments in resilience . Beyond cost‐recovery incentives, systems‐of‐systems engineers can design facilities for supply component availability, surge production, and other commitments to more robust supply chains. Firms that plan for supply chain disruptions can expand their market shares during and after emergencies, while other firms decline or fail entirely. System designs for greater resiliency may reward firms that overcome system shocks, even when resiliency investments are not automatically priced into goods sold or services delivered.